Study of Physical Properties, Chemicals and Sensory with Various Gum Additional Variation in Beetroot (Beta vulgaris L.) with Addition of Cinnamon Extract (Cinnamomum burmannii) - Safira; Kawiji; Siswanti (Politeknik NEST, 2024)
This study aims to determine the effect of gum arab concentration and the addition of cinnamon extract to the sensory, physical and chemical properties contained in the beetroot jam (Beta vulgaris L.). This study used Completely Randomized Design (RAL) with 3 treatments based on different concentrations of gum arab. The treatment is: F1 (0.5% gum arab), F2 (1% gum arab), F3 (1.5% gum arab). This research uses 6 analyzes consisting of total dissolved solids, antioxidant activity, water content, water activity, viscosity and sensory test. Statistical analysis of data with ANOVA at α = 5%. The results of analysis showed that the use of gum arab can reduce the amount of water activity contained in the beetroot jam, so the shelf life of the beetroot jam can last longer. In addition, the use of gum arabic in moisture content did not give significant effect to the beetroot jam obtained, while the viscosity, the total amount of dissolved solids, the antioxidant activity had a significant effect with the addition of gum arab concentration. The optimal use of gum arab was obtained at 1.5% gum arab concentration from multiple comparison test. The use of gum arab concentration of 1.5% is the maximum concentration of the use of gum arabic concentration to beet tuber jam. The use of concentration of 1.5% gum arab is very influential on the five parameters used are aroma, taste, texture, color and overalls.